1998
DOI: 10.1677/jme.0.0210307
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acid residues in the C-terminal tail of big endothelin-1 involved in processing to endothelin-1

Abstract: Big endothelin-1 (big ET-1) is converted to 21-amino acid residue endothelin-1 (ET-1) via a specific cleavage at Trp 21 -Val 22 by endothelin converting enzyme (ECE). This conversion is an essential step to produce bioactive ET-1 and represents a regulatory site in the biosynthesis of this potent vasoconstrictor. ECE-1a, a unique membrane-bound enzyme, processes big ET-1 more efficiently than other big ET isoforms, which mainly differ in the C-terminal tail (residues 22-38). In this study, each of the highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a mutagenesis study of selected residues in the C-terminal portion of bigEDN1, substitution of Pro77 (Pro25 numbering from the start of bigEDN1) to alanine resulted in a significant reduction in the conversion of bigEDN1 to EDN1, as assayed in the media of cells transfected with plasmids encoding wild-type or altered preproEDN1 and ECE1. 38 In addition, p.Pro25Alatransfected cells had less total recombinant protein (bigEDN1 plus EDN1) measured in the media than did cells transfected with wild-type preproEDN1, suggesting that this proline might play a role in bigEDN1 stability. These data argue that the p.Pro77His substitution in individual S1 is pathogenic.…”
mentioning
confidence: 98%
“…In a mutagenesis study of selected residues in the C-terminal portion of bigEDN1, substitution of Pro77 (Pro25 numbering from the start of bigEDN1) to alanine resulted in a significant reduction in the conversion of bigEDN1 to EDN1, as assayed in the media of cells transfected with plasmids encoding wild-type or altered preproEDN1 and ECE1. 38 In addition, p.Pro25Alatransfected cells had less total recombinant protein (bigEDN1 plus EDN1) measured in the media than did cells transfected with wild-type preproEDN1, suggesting that this proline might play a role in bigEDN1 stability. These data argue that the p.Pro77His substitution in individual S1 is pathogenic.…”
mentioning
confidence: 98%
“…It has been shown that the His 27 ‐Gly 34 sequence in big ET‐1 is important for enzyme recognition and conversion to ET‐1 (Okada et al. , 1991; 1993; Brooks and Ergul, 1998). Our strategy avoids labelling within this His 27 ‐Gly 34 region, permitting both enzymic cleavage and formation of [ 18 F]‐ET‐1.…”
Section: Discussionmentioning
confidence: 99%
“…All three endothelins follow a similar pattern of biosynthesis with initial synthesis as precursor proteins (]200 amino acid residues) which undergo selective proteolysis to yield the biologically inactive intermediates called big endothelins (Yanagisawa et al 1988, Bloch et al 1989, Ohkubo et al 1990). The active endothelins are generated by hydrolysis of the Trp 21 -Val 22 bond in big ET-1 and big ET-2, or Trp 21 -Ile 22 in big ET-3 (Brooks & Ergul 1998). This cleavage is unique to the endothelins and hence the role of a specific endothelin-converting enzyme (ECE) was proposed (Yanagisawa et al 1988).…”
Section: Introductionmentioning
confidence: 99%